Dual use and gain-of-function research: a significant endeavor with biosecurity imperatives - James Giordano; Diane DiEuliis (mSphere, 2025)
ABSTRACT The current U.S. administration has recently proposed a pause on all domestic gain-of-function (GoF) research in order to fully revise existing policy. However, domestic controls on GoF research cannot mandate that other nations follow suit and thus do not prohibit non-compliant nations from engaging in such work. In fact, such national constraints may facilitate opportunities for competitor and adversarial nations (and non-state actors) to advance efforts in this space toward nefarious applications. Moreover, certain groups may argue that GoF research may be necessary for advancing biomedical science (A. Casadevall, F. C. Fang, and M. J. Imperiale, mSphere 9:e00714-23, 2024, https://doi.org/10.1128/msphere.00714-23) and global health security and, through this stance, conduct GoF research that has direct dual-use viability. In this light, we argue that all GoF research should be conducted under a robust framework of enhanced BSL controls that explicitly define its dual usability, classify any such enterprise as DURC, engage regulatory oversight, and establish ethical responsibility within the scope and tenor of international law. This essay describes the possible burdens and risks of GoF research, and in addressing the challenges posed by such work, proposes recommendations for future policy toward sustaining beneficial outcomes and preventing or mitigating threats to public health and global biosecurity.